Interest in a short psychological intervention in patients with psoriasis: a cross-sectional observational study at a German clinic - Stadtmüller, Laura R.; Eckardt, Markus A.; Zick, Christoph; Kupfer, Joerg; Schut, Christina (Frontiers in Medicine, 2023)
Introduction Utilization of health services is not only associated with the kind of illness one has, but also with patient characteristics like age, sex or psychological variables. Psoriasis (PS) is a chronic inflammatory skin condition, in which psychological interventions were shown to be beneficial regarding not only psychological variables, but also regarding the skin status. The present study investigated with regard to which patient characteristics PS-patients with interest in participation in a short psychological intervention differ from PS-patients without interest. Methods This cross-sectional questionnaire study was conducted at a German rehabilitation clinic. At the beginning of their stay at the clinic, 127 PS-patients filled in questionnaires to assess the severity of their PS, stress, illness perceptions, mindfulness, anxiety, and depression. Interest in taking part in a short psychological intervention was assessed using a dichotomous item. The statistical analysis comprised group comparisons using t-tests of patients with and without interest to take part in a short psychological intervention. Results Sixty-four of the participants were male (50.4%). Participants were 50.7 ± 10 years on average (range: 25–65). 50.4% of them had a mild, 37.0% a moderate, and 12.6% a severe PS. Results indicated that patients with interest in a short psychological intervention were younger, reported to have more skin symptoms due to their PS (higher skin-related illness identity), were more anxious and depressed, but less stressed and less mindful than patients without interest. Conclusion This study shows that in PS-patients with certain characteristics, it might help to raise awareness on the relationship between psychological factors and symptoms of the skin disease in order to motivate this group of patients to take part in psychological interventions to improve their skin condition. Further studies are needed to investigate whether patients who show interest in a psychological intervention also actually take part in the intervention and profit from it. Clinical Trial Registration: DRKS00017426.